The case against the arts from Plato to Tolstoy and its implications for why and how the arts should be taught in schools. Issue 1 (2nd January 2016) - Tate, Nicholas
Abstract : From Plato onwards many of the great Western thinkers have explored the nature of the arts, their contribution to society and their role in education. This has often involved a discussion of the potentially negative impact of the arts. The recurring message has been that the arts can warp judgment, elevate emotion at the expense of reason, distract people from attending to their own lives, diminish autonomy and authenticity, and create a damaging culture of fame. This "case against the arts" has been associated with the wish to control their contents and restrict their use in education. The views of Plato, Aristotle, Augustine, Rousseau and Tolstoy are considered in turn and distinctions made about the extent to which each writer's "case against the arts" is a "case against the arts" per se or only against certain kinds of arts. Four implications for arts education are discussed: the avoidance of hyperbole with regard to the benefits of arts education; the role of cognition in responding to the arts; the ethical dimension of art appreciation; and the balance between practice and study. The conclusion is that the "case against the arts" provides a powerful case for arts education of a certain kind.